PEMANFAATAN KELAS DIGITAL TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA ABI HURAIRAH PERAK - Zaki Ahmad Fauzan; Muhamad Khoirur Roziqin; Chusnul Chotimah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to determine the effect of digital classroom utilization on students’ learning achievement in the subject of Islamic Religious Education and Character Education at SMA Abi Hurairah Perak. The background of this research stems from the need for digital-based learning innovation to improve the effectiveness and outcomes of students’ learning in the modern era. This research used a quantitative approach with an experimental method. The population consisted of all tenth-grade students of SMA Abi Hurairah, totaling 20 students, selected using a total sampling technique. Data were collected through questionnaires, tests (pre-test and post-test), and documentation of students’ academic records. Data analysis employed descriptive and inferential statistics, including validity, reliability, and Product Moment correlation tests using SPSS Statistics 23. The results showed that the use of digital classrooms had a positive and significant effect on students’ learning achievement in Islamic Religious Education and Character Education. The average score of digital classroom utilization was 39.9 (high category), while the average student achievement score was 39.9 (very high category). These findings indicate that digital classrooms effectively enhance students’ motivation, engagement, and academic performance.